Social media engagement of citizens in developed city during the Covid-19 pandemic (The Journal of Medicine, Humanity and Media, 2024)
During the Covid-19 lockdown period, the physical barriers of large, developed cities have affected the citizens' lives who have long relied on Internet technology to maintain the operation of social order. In this dilemma, with the help of social media, individual citizens or groups taking the community as a unit act spontaneously to carry out group purchase of goods, deployment of epidemic prevention and control, mutual assistance among citizens. The semi-public sphere built by WeChat group chat has become a social media platform to maintain citizen practice. In this semi-public sphere, there are interwoven with non-benefit obtaining citizen opinion leaders and passively participating citizen individuals. Citizen opinion leaders have expanded the generation and extension of temporary, micro and spontaneous citizen actions in the semi-public sphere. Citizen actions and citizen mutual assistance have alleviated the material shortage and mental anxiety of the public in the Covid-19 lockdown. At the same time, the semi-public sphere formed by relying on social media such as WeChat is not developed for all citizens. The digital exclusivity presented by social media makes it difficult for many people with low digital contact (the elderly, the disabled, etc.) to obtain the right to maintain their own interests in the practice of citizen action to a certain extent. Although social media can accurately obtain the personalized needs of different users by relying on digital technology and big data algorithms, the physical space barrier caused by the Covid-19 lockdown has further blocked the opportunities for low digital contact people to learn social media, widened the digital divide, and further unbalanced and non-universal citizen participation in the semi-public sphere.
Keywords: Social-media; citizens' lives; covid-19; civil rights